1998
DOI: 10.1107/s090744499800122x
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structure of Human Lysozyme Labelled with 2',3'-Epoxypropyl β-Glycoside of Man-β 1,4-GlcNAc. Structural Change and Recognition Specificity at Subsite B

Abstract: Human lysozyme (HL) labelled with the 2',3'-epoxypropyl ,8-glycoside of Man-,81,4-GlcNAc was crystallized at pH 4.5. The cell dimensions were a --36.39, b = 116.38, c= 30.91 ,~, and the space group was P2k2121. The unit cell contained four molecules (V,,, = 2.18 A 3 Da-l). The crystal structure was determined by molecular replacement and refined to an R value of 0.168 for 7060 reflections [IF,,[ > 3o(F)] in the resolution range 8.0-2.1 .~,. A prominent shift of the C"-atom positions by up to 3.8/k in the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…However, to date, only a few cases, in which the three-dimensional structure of the modified enzyme was determined at high resolution, have been reported with regard to glycosidases (Keitel et al, 1993;Chen et al, 1995;Havukainen et al, 1996). The modified human lysozyme (HL) that uncovered the origin of its carbohydrate-recognition specificity has also constituted part of the limited examples (Muraki et al, 1996(Muraki et al, , 1998(Muraki et al, , 1999(Muraki et al, , 2000a. C-type lysozymes including HL and hen egg-white lysozyme (HEWL) are a family of bacteriolytic enzymes of vertebrate origin.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, only a few cases, in which the three-dimensional structure of the modified enzyme was determined at high resolution, have been reported with regard to glycosidases (Keitel et al, 1993;Chen et al, 1995;Havukainen et al, 1996). The modified human lysozyme (HL) that uncovered the origin of its carbohydrate-recognition specificity has also constituted part of the limited examples (Muraki et al, 1996(Muraki et al, , 1998(Muraki et al, , 1999(Muraki et al, , 2000a. C-type lysozymes including HL and hen egg-white lysozyme (HEWL) are a family of bacteriolytic enzymes of vertebrate origin.…”
Section: Introductionmentioning
confidence: 99%
“…The shift slightly widened the substrate binding cleft, which was not observed in the single labeling of HL with Gal-1,4-GlcNAc-Epo. A larger shift of this region has been observed in the labeling of HL with Man-1,4-GlcNAc-Epo (22).…”
Section: Resultsmentioning
confidence: 89%
“…The structural analyses of the products indicated that all disaccharides in the labeled HLs occupied essentially the same position designated as subsites B and C (21,22). The lysozyme-saccharide complex has been extensively studied by X-ray crystallography (6).…”
mentioning
confidence: 99%
“…The binding mode of N-acetylglucosamine residue at subsite C was totally maintained, therefore the site-specific labeling reactions were considered to proceed via the recognition of N-acetylglucosamine residue at subsite C. The inactivation of lytic activity against M. luteus cells substrate occurred by the conjugation. The half lifetime of residual lytic activity of human lysozyme in the presence of 2', 3'-epoxypropyl β-glycosides of Gal-β1, 4-GlcNAc and Man-β1,4-GlcNAc was prolonged by approximately twice as much compared with the corresponding derivative of GlcNAc-β1, 4-GlcNAc [47]. This clearly presented the weaker affinity of the former two derivatives than the latter one, which should be ascribed to the difference in the affinity at subsite B.…”
Section: Extensive Protein Engineering Studies Concerning Catalytic Mechanism and Enzymatic Activitymentioning
confidence: 96%
“…X-ray structural analysis of site-specifically conjugated derivatives of disaccharides: In order to further examine the functional role of the interactions between the carbohydrate residue bound at subsite B and Tyr63 residue in the ligand recognition event in human lysozyme, human lysozyme derivatives site-specifically conjugated with 2', 3'-epoxypropyl β-glycoside derivatives of three kinds of disaccharides, namely N-acetylchitobiose (GlcNAc-β1, 4-GlcNAc), N-acetyl lactosamine (Gal-β1, 4-GlcNAc) and β-1, 4 linked mannosyl N-acetylglucosamine (Man-β1, 4-GlcNAc), were synthesized. The detailed structures of these three kinds of site-specifically labeled human lysozymes were analyzed by X-ray crystallography [46,47]. All conjugations were conducted by the ester linkage formation with the side-chain carboxylate group of Asp53.…”
Section: Extensive Protein Engineering Studies Concerning Catalytic Mechanism and Enzymatic Activitymentioning
confidence: 99%